The influence of entrepreneurial literacy and intention through motivation on the students entrepreneurial readiness in university - Saukani Saukani; Muazza Muazza; Firman Firman; Yesi Elfisa (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Entrepreneurship is very important in advancing the economy. The ratio of the number of entrepreneurs in Indonesia is still 3.47 percent. When compared with neighbouring countries, such as Singapore at 8.76 percent, Malaysia at 4.74 percent, and Thailand at 4.26 percent. For this reason, it is necessary to increase the readiness of the younger generation, especially students, in entrepreneurship. The aim of the research is to examine the influence of literacy and intention through motivation on the entrepreneurial readiness of Merangin University students. This research uses a quantitative approach with a correlational survey method to test the influence between variables. A total of 285 students were sampled. This research data was tested using Structural Equation Modelling (SEM). The research results show that: 1) literacy, intention, motivation influence students' entrepreneurial readiness; 2) literacy, intention influences students' entrepreneurial motivation; 3) motivation cannot mediate the relationship between literacy and students' entrepreneurial readiness; 4) motivation can mediate the relationship between intentions and students' entrepreneurial readiness. This research encourages changes in higher education policies. The findings of this research are that knowledge and skills and entrepreneurial spirit can strengthen entrepreneurial readiness and the need for implementing entrepreneurial practices for students.